Primary Retinal Cultures as a Tool for Modeling Diabetic Retinopathy: An Overview. (19th January 2015) - Matteucci, Andrea; Varano, Monica; Mallozzi, Cinzia; Gaddini, Lucia; Villa, Marika; Gabrielli, Sara; Formisano, Giuseppe; Pricci, Flavia; Malchiodi-Albedi, Fiorella
Abstract : Experimental models of diabetic retinopathy (DR) have had a crucial role in the comprehension of the pathophysiology of the disease and the identification of new therapeutic strategies. Most of these studies have been conducted in vivo, in animal models. However, a significant contribution has also been provided by studies on retinal cultures, especially regarding the effects of the potentially toxic components of the diabetic milieu on retinal cell homeostasis, the characterization of the mechanisms on the basis of retinal damage, and the identification of potentially protective molecules. In this review, we highlight the contribution given by primary retinal cultures to the study of DR, focusing on early neuroglial impairment. We also speculate on possible themes into which studies based on retinal cell cultures could provide deeper insight.